Evaluasi Implementasi Pembelajaran STEM Berbasis Project Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah dan Keterampilan Kolaborasi Siswa Sekolah Dasar: Evaluasi Implementasi Pembelajaran STEM Berbasis Project Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah dan Keterampilan Kolaborasi Siswa Sekolah Dasar - Risnawati risnawati; Neni Hermita; M. Jaya Adi Putra (STKIP Subang, 2025)
The implementation of STEM learning in primary schools is increasingly recommended to meet the skills needs of the 21st century, especially critical thinking, problem solving, and collaboration skills. However, implementation in the field does not always run smoothly, especially when students do not yet have experience with project-based learning. This study aims to evaluate the implementation of STEM-PjBL learning in Grade IV elementary school by examining the obstacles that arise, the effectiveness of corrective actions through classroom action research (CAR), and the extent to which teacher mentoring strategies can increase student engagement and collaboration. The research method used two cycles of classroom action research (CAR) involving 28 students. Data were collected through collaboration rubrics, project assessment rubrics, observation sheets, and student reflections. The results showed that in cycle I, students still experienced difficulties such as an imbalance of roles within groups, the dominance of certain members, and confusion in following the STEM project flow. However, after the implementation of structured scaffolding, clearer instructions, and a more systematic division of roles, there was an increase in student engagement and project quality in cycle II. Collaboration scores increased by approximately 24–28%, and product quality improved by 30%. These findings confirm that STEM-PjBL learning is highly dependent on instructional design, teacher readiness, and the clarity of assessment tools. This article provides recommendations for more realistic STEM implementation.